Determinants of Bribery and Corruption in Public Service Delivery: A Case Study in Nepal - Joshi, Ganesh Raj; Dangal, Rameshwor (Journal of Management Studies and Development, 2023)
Bribery is a multi-faceted phenomenon prevalent in Nepal's public service delivery. The amount of bribe provided differs by type and nature of services. This paper aims to assess the level of corruption in Nepal. It analyses the additional amount the service receivers supplied to the public officials and their determinants using logistic regression. It uses cross-sectional data collected by the Commission for Investigation of Abuse of Authority in 2017 from 1668 service receivers who received service out of 3400 applicants seeking different public services. It is revealed that the CPI score is 34, which indicates that the level of corruption is high in Nepal. Among the service receivers, 39% provided bribes to public officials and used intermediaries to complete their work, increasing public service costs.  Analysing the determinants of giving fixes shows that gender, education, number of times visiting public offices, perception about the staff behaviour, age and the occupation of the service receiver were significant variables. These findings imply that it is crucial to promote integrity and accountability among public officials by enforcing and monitoring the compliance mechanism and providing different benefits to motivate them to deliver quality services on time. It is equally essential to develop transparent approaches and tools for service delivery.